Analysis of the Factors Influencing MSMEs’ Decisions in Using QRIS Payment Facilities (Study on MSMEs at the Courtyard of the Darussalam Grand Mosque, Soppeng Regency) - Muhammad Luthfi Siraj; Febriana Harsono; Haedar Akib (Public Resource Innovation Management and Excellence, 2026)
This study aims to analyze the factors influencing the decisions of Micro, Small, and Medium Enterprises (MSMEs) in using the Quick Response Code Indonesian Standard (QRIS) payment facility among MSMEs located at the courtyard of the Darussalam Grand Mosque, Soppeng Regency. This research employed a qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The data were analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that perceived ease of use is one of the primary considerations influencing MSMEs in deciding to adopt QRIS, as the payment system is considered simple, practical, and easy to use in transaction processes. In addition, QRIS provides benefits in facilitating cashless transactions and offering alternative payment methods for consumers. However, several MSME actors still choose not to use QRIS due to perceived risks, such as concerns regarding errors in using digital technology and the persistence of consumer habits that still predominantly rely on cash transactions. Therefore, increasing socialization and understanding regarding the use of QRIS is necessary to encourage the adoption of digital payment systems among MSMEs.